Study on the mechanism of miRNA9718 inhibition of the STAT3 pathway exacerbating Candida albicans-induced intestinal epithelial cell damage - Zhao, Jinying; Yin, Liping; Jiang, Linxin; Shen, Sijia; Tang, Jianguo; Yin, Xue (Penerbit Universiti Kebangsaan Malaysia, 2025)
Candida albicans is a commensal yeast pathogen that frequently colonizes the human gastrointestinal (GI) tract, and this capacity to efficiently invade allows it access to deeper tissues leading to disease. Probing this resistance is necessary to develop effective treatment strategies and requires further understanding of how intestinal epithelial cells resist invasion by C. albicans. In this study, we performed miRNA transcriptomic analysis combined with experiments to screen differentially expressed miRNAs under C. albicans exposure in intestinal epithelial cells. We also identified a subset of miRNAs that were notably deregulated by C. albicans invasion, largely within the context of targeting STAT3. Taken together, we provide new insights on how intestinal epithelial cells counteract C. albicans invasion. The STAT3 pathway and its regulation of the dysregulated miRNAs are evidenced by our studies. These results further the progress in intestinal host-pathogen interaction and has implications for possible C. albicans directed therapeutics approaches.